PELATIHAN PEMBUATAN GIFT PIGURA DENGAN BUNGA UNTUK MENINGKATKAN KREATIFITAS WARGA - herni herni febriana fatimah; Dewi Ariyani Dewi Ariyani (Universitas Negeri Surabaya, 2022)
Keniten Village is one of the villages in the Kedungbanteng sub-district which has a large number of productive age population, but this is not accompanied by community productivity, it is proven that there are still many residents who do not have the skills or jobs. Therefore, skills training was made to the community regarding making handicrafts. The examples of crafts made are in the form of Gift Frames so that people are more productive and increase creativity and skills. This training activity was carried out in August 2021 by involving 5 housewives in Keniten Village. The activity begins by giving an explanation of the training material, followed by mentoring in the practice of making Gift Frames, and ends with an evaluation and checking of results. The purpose of this training activity is as an effort to improve the skills of the Keniten Village community in making Gift Frame handicrafts. The results of the evaluation can be seen that almost all participants have a good level of understanding about how to make Gift Frames. The average ability of the participants to understand, although there are still some people who find it difficult to understand this training. So that this training can be said to be successful and can be applied. Suggestions given by participants include, the type of flower used should be smaller than before so that the frame is easy to decorate. Then for the frame you should use a larger size.